2019
DOI: 10.1002/jpln.201900243
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon and nutrients in smallholding land uses in southern Ethiopia

Abstract: This study assessed the soil organic C (SOC) and soil nutrients in smallholding home garden, woodlot, grazing land, and cropland at two soil depths and two sites in Wolaita Zone, southern Ethiopia. The results showed that soil properties were significantly influenced by land use. The home garden had significantly higher (p < 0.05) SOC and soil nutrients when compared to the cropland. When the home garden was compared to the woodlot and grazing land uses, it had significantly higher (p < 0.05) values except in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, the lowest MBC in the grazing land and home garden suggests the lower P sorption capacity with increasing P concentrations in the soil. e organic matter input in the home garden and manure from grazing livestock in grazing land could contribute to the higher SOC [17]. us, less buffered soil can supply high P to soil solution due to higher SOC, of the mineralization as well as interference with sorption, supplies a relatively higher P to the soil solution [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lowest MBC in the grazing land and home garden suggests the lower P sorption capacity with increasing P concentrations in the soil. e organic matter input in the home garden and manure from grazing livestock in grazing land could contribute to the higher SOC [17]. us, less buffered soil can supply high P to soil solution due to higher SOC, of the mineralization as well as interference with sorption, supplies a relatively higher P to the soil solution [33].…”
Section: Discussionmentioning
confidence: 99%
“…e soil sample was air-dried, ground with mortar and pestle, and passed through a 2 mm sieve. e soil parameters: pH, OC (organic carbon), clay, AP (available phosphorous), and CEC (cation exchange capacity) were determined as presented in Lulu et al [17]. Dithionate-citrate-bicarbonate (DCB) extractable Fe, Al, and Mn oxides (Fe d , Al d , and Mn d ) were determined by the method described by Mehra and Jackson [18].…”
Section: Analysis Of the Soil Samplesmentioning
confidence: 99%
“…In all it is estimated that 40% of Ethiopia’s arable lands are acidic [ 11 ]. More recent assessments have indicated that soil acidity is expanding in scope and magnitude in Ethiopia, seriously affecting crop production [ 15 ]. For example, in some barley, wheat and fava bean growing areas of central and southern Ethiopian highlands, farmers have shifted to producing oats that are more tolerant to soil acidity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%